E-043 Natural history and treatment outcomes of distal anterior cerebral artery aneurysms: a retrospective review. (23rd July 2022) - Lawrence, M; Alwakeal, A; Golnari, P; Nazari, P; Jahromi, B; Potts, M
Abstract : Background: Distal anterior cerebral artery (dACA) aneurysms are rare and their natural history is not well known. We sought to evaluate the natural history and treatment outcomes of these aneurysms through a single institution retrospective review. Methods: We conducted a retrospective review of all dACA aneurysms managed at our institution between 1999 and 2021. Patient demographics, presentation, aneurysm characteristics, management details, and outcomes were collected. Results: We identified 116 patients with 123 dACA aneurysms. Mean age was 58.7 years and 74% were female. Aneurysm risk factors include hypertension (69%), smoking (55%), and a family history of cerebral aneurysms (8%). Seven patients (6%) had bilateral dACA aneurysms while 54% had at least one additional non-dACA aneurysm. Thirty-five patients (30%) presented with aneurysm rupture – 22 (18%) of which were caused by a dACA aneurysm while the rest were caused by a separate aneurysm. Aneurysm laterality was left in 47% and right in 38%, while 15% arose from an azygos ACA. The majority of dACA aneurysms (63%) arose from the A3 (precallosal) ACA. The mean maximal aneurysm dimension was 4.2 mm while the mean aspect ratio was 1.2. The mean maximal dimension to parent vessel diameter ratio was 2.4. Sixty-nine patients with 72 aneurysms were initially managed conservatively, comprising a 'natural history' cohort, with a mean of 33 months of angiographic follow-up. During this time, there were three instances of documented growth. Ultimately, 64 patients underwent treatment with microsurgical clipping (47 patients with 50 aneurysms) or endovascular coiling (17 patients with 19 aneurysms) with a mean angiographic follow-up of 38.8 months. During this time, there were two instances of recurrence after coiling, one of which required retreatment. Significant differences in dACA aneurysms presenting with rupture versus those without rupture included maximal dimension (p=0.03) and maximal dimension to parent vessel diameter ratio (p=0.01). Conclusions dACA aneurysms are rare. They are typically small in size and most commonly arise from the precallosal ACA. Size and the ratio between size and parent artery diameter are significant factors between ruptured and unruptured dACA aneurysms. They can be successfully treated with both microsurgical and endovascular techniques. Disclosures: M. Lawrence: None. A. Alwakeal: None. P. Golnari: None. P. Nazari: None. B. Jahromi: None. M. Potts: None.